PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, KOMITMEN ORGANISASI DAN DISIPLIN KERJA TERHADAP PRESTASI KERJA KARYAWAN PADA PT.VALUPAK OLI SINGER GEDANGAN SIDOARJO - Harline Trismawati (Research Parks Publishers, 2020)
Human resources are seen as vary important in the success of the organization because of human resources is not merely about what defined the human resource, but what is produced by these resources. In this study, the initial observations of the researchers they that transformational leadership style, organizational commitment and discipline work already influential significantly to achievement of work. However, there are indications of employee accomplishments is dwon. This type of research using a quantitative approach. The population in this research is the existing employees at PT. Valupak Oli Singer Sidoarjo Gedangan. With the sampling techniques used in this research is a probability sampling method using random sampling. Analytical techniques used in this research is the analysis of multiple regression. As for the goal in this research is to find out whether Transformational Leadership, organizational commitment and discipline Work Against Accomplishment of work. Both simulta or partial.. Based on the research results obtained proved that influential Work most significant Discipline against employees on work achievement PT. Valupak Oli Singer Sidoarjo Gedangan.